A Possible Approach for Stem Cell Gene Therapy of Fanconi Anemia - Song, Liting (Current Gene Therapy, 2009)
Fanconi anemia (FA) is an inherited chromosomal recessive syndrome characterized by cellular hypersensitivity to DNA crosslinking agents and bone marrow failure, which cause aplastic anemia, and an increased incidence of malignancy. 13 complementation groups are currently discovered, and 13 distinct genes have been cloned (FANCA, FANCB, FANCC, FANCD1, FANCD2, FANCE, FANCF, FANCG, FNACI, FANCJ, FANCL, FANCM, FANCN). Stem cells can theoretically divide to other cells without limit as long as a person is still alive. The stem cells that form blood and immune cells are known as hematopoietic stem cells. Hematopoietic stem cells can be acquired from a Fanconi anemia patient, whereas genomic DNA can be obtained easily from blood cells of a normal person. Normal genes also can be synthesised by PCR method. Normal genomic DNA will be delivered into a patient's stem cells via microinjection or transfection after enzyme digestion; the defective genes might be repaired by homologous genetic recombination. The gene-corrected stem cells can be transplanted into the same patient finally. It is possible that human genomic DNA to be considered as materials for homologous genetic recombination to repair defective genes in vivo. This might be an efficient method for gene therapy, which has no or less immunological rejection for Fanconi anemia and some genetic diseases. Several related observations and experiments are discussed to support this possible means of stem cell gene therapy of Fanconi anemia.
Keywords: Homologous genetic recombination